Numerical models of hydrodynamics and marine debris in the Malacca Strait. Issue 1 (November 2021) - Ondara, K; Purnawan, S
Abstract: The Malacca Strait is a very strategic world trade route and the potential for environmental pollution is also very large, especially pollution from ship and people activities. This study aims to perform numerical simulations to determine the movement of marine debris particles around the waters of Rupat Island, Malacca Strait. The modelling was carried out from June to December 2020 using a modelling application with the basic principles of mesh discretization and the Lagrangian method. The results showed maximum current velocity during the simulation around the distribution area of debris is a maximum of 0.92 m/s. Marine debris around the waters of Rupat Island, the Malacca Strait has the potential to be stranded on the mainland of Rupat Island, mainland Riau, Bengkalis Island and also mainland Malaysia.